Geographic Information System for Mapping the Potency of Batik Industry Centre - Taryadi Taryadi; Sattriedi Wahyu Binabar; Dicke JSH Siregar (Universitas Airlangga, 2019)
Background: As one of batik producer city in Indonesia, Pekalongan city needs medium and infrastructure that able to provide the information needed by either the local government or the society. The need about information of Batik city center in Pekalongan will provide the information about the batik center for the local government in the potency, obstacle and the needs of Small and Medium Batik Enterprises Centre to improve the Batik Production.Objective: The research is aimed at mapping the potency of batik center in Pekalongan city by implementing Geographic Information System Technology. The information about batik center in Pekalongan city needs to be maintained. The maintenance in information field is needed upon the batik center in Pekalongan.Methods: The method used in mapping the batik potency in Pekalongan city is the Geographic Information System (GIS) by providing the information based on a spatial data. Whereas the waterfall system development is used in developing the GIS.Results: The research resulted the application in mapping the batik center with GIS based that provide reference to the related parties about information and planning as well as investment in batik business.Conclusion: The system is able to provide the information needed by users, such as business mapping, the mapping about the amount of business in one area, the batik potency in each district that is figured for mapping location.